Neonatal pneumonia in a rural primary care hospital in Bangladesh: prevalence, validation of clinical features and their outcome (Bangladesh Critical Care Journal, 2016)
Objective: To explore prevalence, validity of associated factors and their outcome of pneumonia in neonates.Methods: We retrospectively enrolled neonates admitted to a rural hospital in Bangladesh from January 2012-December 2014. Those with pneumonia constituted cases (n=142) and randomly selected three folds of cases from those without pneumonia formed the controls (n=426). Pneumonia was diagnosed by hospital physicians based on respiratory difficulty and/or abnormal auscultatory findings in lungs.Result: The deaths were significantly higher among the cases than the controls (p=0.025). In logistic regression analysis, fast breathing, lower chest wall in-drawing, adventitious sound and cough were independently associated with neonatal pneumonia (for all, p